INTERNALIZING THE VALUE OF MORAL BELIEFS IN EARLY CHILDHOOD THROUGH DAILY ACTIVITIES AT HUSNA JAYA KINDERGARTEN SEMARANG: internalisasi nilai akidah akhlak pada anak usia dini melalui kegiatan harian di TK Husna Jaya semarang - Anisa Alfiani; Agus Khunaifi; Mursid (SOSIOEDUKASI, 2025)
Instilling the values of faith and morals in early childhood is a strategic step in shaping Islamic character from an early age. This study aims to describe the internalization of moral values through daily activities at Husna Jaya Kindergarten Semarang. The research method uses literature studies and simple observations on habituation practices in schools. From the results of the literature review, it is known that the internalization of the value of moral beliefs can be carried out through habituation, example, and strengthening of exemplary stories from the Prophet and previous Islamic figures. The subjects of the research were students of Husna Jaya Kindergarten, especially 25 children aged 5-6 years. Observations were carried out for 2 weeks and observations were non-intrusive participants. The analysis technique is descriptive qualitative with a thematic content analysis approach and data triangulation. The results of observations at Husna Jaya Kindergarten Semarang show that the implementation of internalizing moral values is carried out simply through the habit of saying four magic words, namely sorry, thank you, please, and excuse me. This habit is repeated in various daily activities, such as playing, studying, and interacting with teachers and peers. In addition, teachers also use the example method by telling exemplary stories from the time of the Prophet and his companions, so that children can imitate the good attitude exemplified. The internalization of these values is not carried out formally, but through activities that are fun and close to the child's daily life. Thus, it can be concluded that simple strategies in the form of habituating polite speech and delivering exemplary stories can be an